Correlates of Entrepreneurial Intention among Students with Neurodevelopmental Disorders - Chiedu Eseadi; Aaron A. Phillip; Hero U. Obasuyi; Chimezie F. Obilezuru; Christian S. Ugwuanyi; Chinedu A. Ugwuanyi (Kuras Institute, 2023)
This study aimed to investigate the correlates of entrepreneurial intention among a sample of high school students with neurodevelopment disorders. The study was conducted using a correlational survey research design. The research data were collected from one hundred college students diagnosed with neurodevelopmental disorders through the use of a questionnaire. The study findings indicated that attitude, subjective norms, and perceived behavioral control of these students with neurodevelopmental disorders were significantly linked to their entrepreneurial intention. The results of this study demonstrate the significance of the Theory of Planned Behavior in analyzing the entrepreneurial intention of Nigerian high school students diagnosed with neurodevelopmental disorders. It is critical for career counselors to assist students with neurodevelopmental disorders in identifying the skills or resources needed to succeed as entrepreneurs. Career counselors should guide them on how to mitigate any difficulties they might experience in finding an appropriate business venture that takes into account the severity of their disability.